Laser-free pelvic alignment in an online adaptive radiotherapy environment. (March 2020) - Barnes, Helen; Mohajer, Jonathan; Dunlop, Alex; Adair Smith, Gillian; Herbert, Trina; Lawes, Rebekah; Tree, Alison; McNair, Helen
Highlights: The MR Linac is a novel laser-free online adaptive radiotherapy environment. An audit of MR Linac pelvic set-up accuracy and time was conducted to establish a new standard of practice. Pelvic patient positioning without calibrated lasers produces the level of accuracy required to perform online adaptive MR Linac treatments. Abstract: The MR-Linac (MRL) provides a novel treatment modality that enables online adaptive treatments, but also creates new challenges for patient positioning in a laser-free environment. The accuracy and duration of prostate patient set-up on the MRL using two different methods for patient alignment was determined to establish standard of practice on the MRL. Differences in set-up accuracy were significant in the longitudinal direction and are accounted for in online plan adaption. Both methods recorded similar set-up times. The vendor recommended alignment method involves less manipulation of the patient and will be adopted as the standard positioning method for prostate and other pelvic patients on the MRL in future.